Adhesion and kinetics of biofilm formation and related gene expression of Listeria monocytogenes in response to nutritional stress. (June 2022) - Wang, Yuan; Sun, Linjun; Hu, Lili; Wang, Zhen; Wang, Xiang; Dong, Qingli
Graphical abstract: Highlights: DTSB-YE(nutrition deficiency) enhances initial attachment and subsequently promotes biofilm formation. The dynamics of biofilm formation of Lm83 under nutritional stress were further determined by SEM and EPS analysis. The effects of nutrition deficiency on the expression of critical biofilm-associated genes of Lm 83 planktonic and biofilm cells in TSB-YE and DTSB-YE were measured for the first time. Better cell motility in nutrient deficiencies might facilitate the nutrient acquisition. Abstract: Listeria monocytogenes is a gram-positive pathogen, that usually adheres to stainless steel (SS), and other abiotic surfaces in food processing that undergo repeated cleaning and cause the spread of Listeria . Through the enumeration of biofilm cells, extracellular polymeric substance (EPS) component and the scanning electron microscopy (SEM) analysis of biofilms, it was found that the ratio of cells and extracellular matrix is affected by nutrition status. Regardless of the temperature, all strains exhibited a higher adhesion ability when exposed to 10-fold diluted TSB-YE (DTSB-YE, nutrition deficiency). Three hour initial adhesion was significantly positively correlated with biofilm formation ( p ＜0.01). DTSB-YE enhances initial attachment and subsequently promotes biofilm formation. The SEM analysis also showed that in DTSB-YE the adhesion and covered area of the attached cells were higher than those in TSB-YE (rich media). The amount of both extracellular polysaccharides and proteins was significantly higher when incubated in DTSB-YE than TSB-YE. The highest biofilm formation of Lm83 was observed in DTSBYE independent of temperature. The effects of nutrition deficiency on the expression of critical biofilm-associated genes of Lm 83 planktonic and biofilm cells were measured. The gene expression levels of inlA and sigB in biofilm cells in TSB-YE and DTSB-YE were approximately 95.7% and 88.0% and 42.2% and 45.7% lower than those in planktonic cells, respectively. However, the expression of inlA in DTSB-YE was significantly higher ( p ＜0.05) than that in TSB-YE for the same cell state. Interestingly, the gene expression of motB was considerably higher in DTSB-YE than in TSBYE, regardless of the state. These results indicate that better cell motility in nutrient deficiencies might facilitate the cell aggression to promote biofilm formation.